Missed aortic valve endocarditis resulting in complete atrioventricular block and redo mechanical valve replacement - Harky, Amer; Garner, Megan; Popa, Miruna-Andrea; Shipolini, Alex (BMJ case reports, 2017)
Infective endocarditis is a rare disease associated with high morbidity and mortality. As a result, early diagnosis and prompt antibiotic treatment with or without surgical intervention is crucial in the management of such condition. We report a case of missed infective endocarditis of the aortic valve. The patient underwent mechanical aortic valve replacement, with the native valve being sent for histopathological examination. On re-admission 16 months later, he presented with syncope, shortness of breathing and complete heart block. On review of the histopathology of native aortic valve, endocarditis was identified which had not been acted on. The patient underwent redo aortic valve replacement for severe aortic regurgitation. We highlight the importance of following up histopathological results as well as the need for multidisciplinary treatment of endocarditis with a combination of surgical and antibiotic therapy.